Development of paediatric critical care in northwestern Nigeria: Initial implementation with a needs assessment model. Issue 3 (May 2022) - Ibrahim, Abdullahi; Scruth, Elizabeth; Adeyinka, Adebayo; Kabara, Halima Salisu; Rivera, Lorena; Hartjes, Tonja; Minso, Jagila; Pierre, Louisdon
Abstract: Introduction: There is high paediatric morbidity and mortality in northwestern Nigeria, attributable in part to vaccine-preventable illnesses and lack of comprehensive training of medical and nursing staff in the healthcare delivery of paediatric critical care. Pediatric Universal Life-Saving Effort Inc. (PULSE), a New York–based nonprofit organisation with a mission to develop paediatric critical care in resource-limited settings, collaborated with Aminu Kano University Teaching Hospital to decrease the gaps in knowledge and skills of medical and nursing personnel. The joint effort also aims to address and remove barriers to the delivery of paediatric critical care in northwestern Nigeria. The primary objective was to perform a needs assessment for paediatric intensive care resources in northwestern Nigeria, identify barriers to delivering these services, and designate a hub for the development of paediatric critical care educational programs for healthcare professionals. Methods: An anonymous survey was designed and distributed using SurveyMonkey® online software to medical and nursing staff from nine healthcare institutions in northwestern Nigeria. Results: Analysis from 67 responses revealed that care delivered to critically ill paediatric patients was by anaesthesiologists (77%), pediatricians (26%), and adult intensive care specialists (10%). The acquisition of clinical skills was perceived to be an essential need (65%), followed by adequate staffing of critical care units (19%), continuing medical and nursing education (13%), and availability of medical equipment (3%). Discussion: There is an identified need for paediatric critical care training and resources in northwestern Nigeria. Conclusion: The needs assessment conducted has provided important results that will form the basis for building staff capacity and training programs for paediatric critical care in northwestern Nigeria.